PEMBUATAN TEH HERBAL DARI DAUN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ) - Tulak Rerung, Lola' (Politeknik Tiara Bunda, 2025)
Tea is one drink that is liked and consumed by people all over the world, containing tannin which is believed to be a refreshing and healthy drink. To make oil palm herbal tea, and know the quality standards bioactive components. Palm leaves are separated from the lid, washed thoroughly, drained, cut ± 1 cm. Furthermore, it is placed on a rack and allowed to wither for 14 to 24 hours, then the leaves are blended and oxidized. Then put it in a cool and humid place, for the fermentation process. Furthermore, it is dried in a drying cabinet with a temperature variation of 50 ° C, 90 ° C and 110 ° C with successive times (110, 130, and 150 minutes) then a quality standard test, and screening of herbal tea powder. Quality standard test of oil palm herbal tea smell, taste and color of distinctive brewing water of tea products, cadmium metal contamination (0.303ppm) and lead (0.149ppm), arsenic contamination (<0.0004ppm), microbial contamination with total plate number11.72 ×107,, water content in a row (7.18; 5.88; 3.92%), extract content in water (8.6; 5.96; 5.76%), total ash content (4.3;4.91; 5.26%), water soluble ash content from total ash (4.62; 7.88; 10.09%), acid insoluble ash content (0.75; 0.93 ; 1.17%). Herbal tea powder screening results were positive for triterpenes/steroids, alkaloids, flavonoids, tannins, saponins, and glycosides. The results of flavonoid test results from fresh leaves of palm oil, powder before drying, herbal tea with drying temperature variations of 50°C, 90° C and 110°C with successive times (110, 130, 150 minutes), namely (357.13;265.678; 175.14; 161.28; 176.99 mg / 100)Oil palm leaf herbal tea can be made as an herbal tea and variationsin drying temperature can affect the quality of the oil palm leaf herbal tea